Market cities, people cities : the shape of our urban future - Emerson, Michael O., 1965-; Smiley, Kevin T. (New York University Press, 2018)
How are modern cities changing, and what implications do those changes have for city inhabitants? What kinds of cities do people want to live in, and what cities do people want to create in the future? Michael Oluf Emerson and Kevin T. Smiley argue that western cities have diverged into two specific and different types: market cities and people cities. Market cities are focused on wealth, jobs, individualism and economic opportunities. People cities are more egalitarian, with government investment in infrastructure and an active civil society.